UPAYA PENINGKATAN KETERAMPILAN KELOMPOK PKK MELALUI PELATIHAN PEMBUATAN NUGET DAGING KELINCI DAUN KATUK KELURAHAN JATI KECAMATAN JATEN - Sukaryani, Sri; Windyasmara, Ludfia; Purwati, Catur Suci; Husein, Muhammad (FKIP Universitas Wisnuwardhana, 2023)
The purpose of the Community Service activity is to introduce rabbit meat to the public as well as to provide knowledge and skills about rabbit meat nuggets with a combination of katuk leaves as a form of innovation in processed rabbit meat. The method of carrying out this activity includes counseling and the practice of making rabbit meat nuggets combined with katuk leaf flour as well as packaging training and marketing strategy training. Prior to counseling and practice, participants were first given a pre-test to determine the level of knowledge and understanding of members of the PKK Rt 03 Rw V about rabbit meat and its processed products. After the counseling and practice activities were completed, the participants were given a post test which was intended to determine the increase/absorption of knowledge and skills provided by the service team from Bantara Sukoharjo Univet. The target participants were 20 members of the PKK Rt 03 Rw V group. The results obtained were that the participants were very enthusiastic in participating in the activities both during counseling and during practice and assistance in the production of nuggets. The average pre-test score of the participants was 48 and the average post-test score was 88.5. The conclusion from this community service activity was that there was an increase in skills in the PKK group by 84.38%.